Unravelling the 2e− ORR Activity Induced by Distance Effect on Main-Group Metal InN4 Surface Based on First Principles - Peng Li; Jiawen Xu; Yaqiong Su (Molecules, 2022)
The p-electron-dominated main-group metals (Sb, Se, In, etc.) have recently been reported to possess excellent oxygen reduction reaction (ORR) activity by means of heteroatom doping into graphene. However, on these main group metal surfaces, other approaches especially the distance effect to modulate catalytic activity are rarely involved. In this work, the origin of excellent 2e− ORR catalytic activity of graphene-supported InN4 moiety by tuning the distance between metallic In atoms is thoroughly investigated by employing the first-principles calculations. Our DFT calculations show that the 2e− ORR catalytic activity strongly depends on the crystal orbital Hamilton population (COHP) between In and O atoms. This work is useful for the rational design of main group metal single atom electrocatalysts.